Legal policy by the National Land Agency of Pekalongan Regency in resolving Dual Certified Land Disputes through non-litigation - Wafda Vivid Izziyana; Andika Yuli Rimbawan; rifqi fatkhul arifin; hanif salmanudin (Universitas Muhammadiyah Gresik, 2022)
The current development of the land situation in Indonesia nowthese is crucial. Land is the basic capital for the state and development to realize the prosperity of the people. In recent years, land disputes have become increasingly complex, whether they are disputes over land area, also disputes over ownership of multiple certificates. Law No. 5 of 1960 concerning Basic Regulations on Agrarian Principles is a breakthrough in ensuring justice and legal certainty, order, and the welfare of the Indonesian people. The land problem is an issue that concerns the most basic rights of the people. The more complex human interests in a civilization will be directly proportional to the higher the potential for disputes that occur between individuals and between groups. Therefore, it is necessary to have regulations and state institutions that specifically regulate and are authorized in the land sector also dealing with the land problems. The National Land Agency (BPN) was formed whose role was to assist and serve to the community to obtain their rights in the land sector in accordance with applicable rules and regulations, also to find a way out if there were land disputes. The problem of dual certificates which is plot of land has more than one certificate with the same object, resulting in legal uncertainty for the holder of land rights. The Cases of dual certificates are still common in several regions in Indonesia. This study uses normative legal research methods combined with empirical legal research methodologies. The location of the research is in BPN Pekalongan regency. The occurrence of dual certificates is influenced by internal and external factors. There are three dual certificate dispute resolutions, namely, Deliberation (negotiation & mediation) Arbitration, and if you do not get a solutions from BPN, then Dispute Settlement through Courts.